Investigation of Mechanical Behavior of Al2O3 Coating on AISI - 316 Steel - Jeevabharathi, S. (International Journal of Psychosocial Rehabilitation, 2019)
In this work the micro structural description and mechanical properties of alumina coated AISI 316 austenitic steel were examined. The microstructure of both coated and un coated specimens of AISI 316 austenitic steel are captured and studied. The corrosion resistance of the materiel is found out using salt spray test and the hardness of the specimen has been found by using Rockwell hardness principle and equipment. Alumina has an excellent ability to hinder the inward diffusion of oxygen and especially above 1000 degrees centigrade. Alumina is the most effective oxide against environmental attacks. When high temperature metallic coating is exposed to an oxygen containing environment, a protective oxide scale is expected to form on the surface of the coating to slow down or even avoid the depletion of alloying elements by hindering the diffusion of metal ions and oxygen through the oxide scale